Compost impact on heavy metals uptake of two crops; Hordeum vulgare L. and Vicia faba L - M. Elmughrbe, Mariam; S. Elhariri, Khadiga; S. Hamouda, Mohamed (Libyan Journal of Science &Technology, 2024)
Compost is a low-cost technology, environmentally friendly process used to treat organic waste. It has been shown to have several positive impacts when applied to soil on plant growth and some improvements on the physical and chemical properties of soil. It also controls the movements and uptake of metals by plants and animals. The plant species Hordeum vulgare L. (Barley) and Vicia faba L. (Broad bean) were used in this study. The organic fertilizer used was obtained from the local market. The results obtained showed that the application of compost in the soil had increased the growth of both Barley and Broad bean. The data obtained clearly illustrated that the compost used increased the concentration of some metals in the soil and plant especially Fe. But; the levels of heavy metals found in Barley and Broad bean were generally low and still below the permissible levels recommended by the Food Agriculture Organization (FAO) and the World Health Organization (WHO). Variations of the metals in the plants and soils were in the order of Fe>Zn>Ni. The Transfer Ratio (TR) of the metals from the soil to plants the values obtained found the following trend Fe>Ni>Zn.